The varieties of historical experience - Palmié, Stephan; Stewart, Charles 1956- (Routledge, 2019)
This book considers how history is not just objectively lived but subjectively experienced by people in the process of orienting their present toward the past. It analyses affectivity in historical experience, examines the digital mediation of history, and assesses the current politics of competing historical genres. The contributors explore the diverse ways in which the past may be activated and felt in the here and now, juxtaposing the practices of professional historiography with popular modes of engaging the past, from reenactments, filmmaking/viewing and historical fiction to museum collections and visits to historical sites. By examining the divergent forms of historical experience that flourish in the shadow of historicism in the West, this volume demonstrates how, and how widely (socially), the understanding of the past exceeds the expectations and frameworks of professional historicism. It makes the case that historians and the discipline of History could benefit from an ethnographic approach in order to assess the social reception of their practice now, and into a near future increasingly conditioned by digital media and demands for experiential immediacy
Keywords: History / Philosophy